2023
DOI: 10.3390/antiox12071339
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional Regulation of the Acer truncatum B. Response to Drought and the Contribution of AtruNAC36 to Drought Tolerance

Abstract: Drought stress is one of the major environmental factors severely restricting plant development and productivity. Acer truncatum B, which is an economically important tree species, is highly tolerant to drought conditions, but the underlying molecular regulatory mechanisms remain relatively unknown. In this study, A. truncatum seedlings underwent a drought treatment (water withheld for 0, 3, 7, and 12 days), after which they were re-watered for 5 days. Physiological indices were measured and a transcriptome se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 51 publications
0
1
0
Order By: Relevance
“…Previous studies reported that the functions of a large number of NAC TFs in different plant species were involved in various processes, including growth [6] and development processes [7] and abiotic stress responses, such as salt and drought resistance [8][9][10]. For example, the overexpression of RcNAC72 [11], ThNAC4 [12], FtNAC31 [10] and AtruNAC36 [13] could enhance drought tolerance in Arabidopsis, and GmNAC12 in Glycine max positively regulated plant tolerance to drought stress [14]. Plant survival rates were significantly improved in ANAC019-, ANAC055and ANAC072-overexpressing Arabidopsis lines compared to the wild type [15].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies reported that the functions of a large number of NAC TFs in different plant species were involved in various processes, including growth [6] and development processes [7] and abiotic stress responses, such as salt and drought resistance [8][9][10]. For example, the overexpression of RcNAC72 [11], ThNAC4 [12], FtNAC31 [10] and AtruNAC36 [13] could enhance drought tolerance in Arabidopsis, and GmNAC12 in Glycine max positively regulated plant tolerance to drought stress [14]. Plant survival rates were significantly improved in ANAC019-, ANAC055and ANAC072-overexpressing Arabidopsis lines compared to the wild type [15].…”
Section: Introductionmentioning
confidence: 99%